Type II Myocardial Infarction: What Do We Know? - Altaweel, Muneera; AlMukhaylid, Sarah; AlAnazi, Faisal; AlRammadan, Abdullah; Altuwaim, Ibrahim (International Journal of Innovative Research in Medical Science, 2022)
Type I myocardial infarction (T1MI) is caused by acute atherosclerotic plaque disruption; in contrast, type 2 myocardial infarction (T2MI) is caused by changes in myocardial oxygen supply or demand in the absence of acute atherothrombosis [1]. T2MI was initially introduced as part of the universal definition of MI (UDMI). It refers to individuals with an increased cardiac troponin (cTn) level but no evidence of ischemic etiology. Most doctors are baffled by the word, and the definition remains inadequate. It’s not TIMI with evidence-based therapy and guidelines, but rather peer review based. Is chest discomfort accompanied by decompensated heart failure, acute anemia, and Pulmonary embolism indicative of myocardial ischemia? Is transitory ST depression a marker of myocardial ischemia in individuals with fast AF, anemia, sepsis, or electrolyte disturbances? The answer to all these questions is unknown or is currently being determined. On the other hand, is it prudent to do coronary angiograms for all patients? While the answer is still uncertain, the response is emphatical NO. Most doctors use clinical judgment.